In vitro Evaluation of Medihoney Antibacterial Wound Gel as an Anti-biofilm Agent Against Ventricular Assist Device Driveline Infections - Qu, Yue; McGiffin, David; Kure, Christina; McLean, Janelle; Duncan, Courtney; Peleg, Anton Y. (Frontiers in Microbiology, 2020)
Objectives: In adult ventricular assist device (VAD) programs in Australian hospitals, Medihoney Antibacterial Wound Gel (MAWG) is routinely used at the skin exit-site of VAD drivelines to prevent infections, however its effectiveness remains unclear. Our aim was to assess antimicrobial activity of medihoney wound gel, using in vitro models that mimic clinical biofilms grown at the driveline exit-site. Methods: Antimicrobial susceptibility testing of MAWG was performed for twenty-four clinical isolates grown under planktonic conditions and four representative strains grown as biofilms. Different antimicrobial mechanisms of MAWG were assessed respectively for their relative contribution to its anti-biofilm activity. A colony biofilm assay and a drip-flow biofilm reactor assay mimicking the driveline exit-site environment were used to evaluate the activity of MAWG against biofilm growth at the driveline exit site. Results: MAWG demonstrated species-specific activity against planktonic cultures [MICs, 5-20% weight/volume (W/V) for Staphylococcus species, 20->40% (W/V) for Pseudomonas aeruginosa and Candida species]. Higher concentrations [MICs, 30->80% (W/V)] were able to inhibit biofilm growth, but failed to eradicate pre-established biofilms. The anti-biofilm properties of MAWG were multi-faceted, with the often-advertised “active” ingredient methylglyoxal (MGO) playing a less important role. The colony biofilm assay and the drip-flow biofilm reactor assay suggested that MAWG was unable to kill biofilms pre-established in a driveline exit-site environment, or effectively prevent planktonic cells from forming adherent monolayers and further developing mature biofilms. Conclusion: Our work suggests a suboptimal effectiveness of MAWG in preventing driveline infections due to biofilm development.